A Sequential Explanatory: The Academic Risk-taking among Tenth Graders in Public Senior High School - Tan, Andrea G.; Contreras, Izzy N.; Barona, Norie Jean P.; Yumul, John Loyd R.; Francisco, Jericho M.; Nabartey, Razvan Chloe G.; Dominado, Noel L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
ABSTRACT This sequential explanatory research aims to determine the academic risk-taking of tenth graders. The result of the study was the basis of the proposed intervention plan to improve their confidence, support, and motivation to take risks in their academics. A mixed-method sequential explanatory design was used, involving 103 tenth graders in one of the public schools in Cluster I Schools Division of Pampanga. The study revealed that fear of failure, lack of support and motivation, discouragement, judgment, and low self-esteem are why they are not taking risks in their academics. Moreover, the study discovered that this is why the participants struggle with their academic curriculum and have less interest in academics. It affects the participant's behaviour and the school's performance. Even though it is difficult to feel supported because of the environment that they have and how their relationships with the people around them actually work, the findings eventually shed light on the factors that contribute to the student's level of academic risk-taking. They need the support and motivation of their families and friends, encouragement to have high self-esteem and to be motivated to take risks without worrying about failure, and the willingness to take risks despite the difficulties that they may encounter so that they will achieve their goals of having good grades and boost their confidence to try new things beyond their capabilities. Therefore, the researchers made an intervention plan to address and improve the student's academic risk-taking behavior. Recommendations included providing better equipment, comprehensive trainings on crisis communication, news writing and cybersecurity, fostering organizational collaboration, and recruiting specialists. Finally, a Course Instructional Guide for Public Affairs Officers was developed and proposed for adoption and implementation to hone their effectiveness in promoting the PCG’s mission and functions.